Contemplating or Acting? Which Immersive Modes Should Be Favored in Virtual Reality During Physiotherapy for Breast Cancer Rehabilitation - Buche, Hélène; Michel, Aude; Piccoli, Christina; Blanc, Nathalie (Frontiers in Psychology, 2021)
Background Even though virtual reality (VR) is more and more considered for its power of distraction in different medical contexts, the optimal conditions for its use still have to be determined in order to design interfaces adapted to therapeutic support in oncology. Objective The objective of this study was to examine the benefits of VR using two immersion methods (i.e., one participatory, one contemplative) and comparing them with each other in a population of women with breast cancer who have undergone breast surgery, during scar massage sessions. Methods In a physiotherapy center, each patient participated in four experimental conditions in a random order: two sessions used virtual immersion (i.e., one participatory and one contemplative), one session proposed musical listening and the fourth one was a standard session care. The impact of the level of patient involvement in the virtual world was apprehended through the evaluation of the feeling of presence; the estimation of elapsed time of the physiotherapy sessions and particular attention was paid to the evaluation of patient emotional state. Results Our study showed an increase in positive emotions (i.e., joy and happiness) and a decrease in anxiety regardless which support methods were offered. Participatory VR created a feeling of more intense spatial presence. Conclusion Our results highlight the importance of the context in which VR should be offered. The presence of the practitioner and his interactions with the patient can provide a context just as favorable in reducing anxiety as the emotional regulation tools used (VR, music). The use of technological tools should be favored when the practitioner is unavailable during the treatment phase or, even, in order to reduce the monotonous nature of repetitive therapeutic sessions.